Outcomes of esophagus substitution in the management of corrosive esophageal injury in three methods; colon interposition, gastric pull up, and reverse gastric tube - Arash khashayar (Shiraz University of Medical Sciences, 2020)
Background: The corrosive esophageal injury would result in mucosal damage related to type, exposure time, and volume of ingested substance ranging from mild burn to severe necrosis. It is usually seen in childhood. Stricture and dysphagia are common. Swallowing problems are due to prolonged stricture and would require surgery. However postoperative problems should also be considered. The purpose of this study was to determine the results of esophagus substitution in the management of corrosive esophageal injury in three methods; colon interposition, gastric pull up, and reverse gastric tube. Methods: In this observational descriptive-comparative study, 50 consecutive patients attending to Mofid children hospital since 2006 to 2016 were enrolled and the results of esophagus substitution in the management of corrosive esophageal injury in three methods; colon interposition, gastric pull up, and reverse gastric tube among them were determined and compared according to other variables. Results: The results in this study demonstrated that 68% required surgery that 82.3% had repeat surgery. Out of them 22 were performed with Gastric Pull up method that was successful in majority of subjects. Esophageal stricture (74%), vomiting (46%), and dysphagia (40%) were most common preoperative problems and dysphagia (46%), stricture (36%), and vomiting (26%) were most common postoperative problems. There were 4 mortality cases. Conclusion: Totally, according to the obtained results, it may be concluded that esophagus substitution in the management of corrosive esophageal injury is effective that Gastric Pull up method is best option.